Development of early warning voltage and frequency fluction system - Israa Amer Dahnam (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2015)
A microcontroller PIC 16F877 - based monitoring circuit was designed, simulated and implemented. The circuit has been intended to monitor main power supply and gives a warning to protect electronic devices against voltage and frequency fluctuations. The circuit was designed to continuously monitor a main power supply and ensure that the main voltage and frequency are within required voltage range (RVR) and required frequency range (RFR). The circuit gives two types of warning buzzer and red light if the voltage and/or the frequency fall below or above the RVR and the RFR respectively. Moreover, the circuit through a relay will disconnect the main power supply if either or both voltage and frequency drop below or above RVR and RFR. Also, the circuit will reconnect the main power supply if both voltage and frequency fall back stable in the RVR and RFR. The software (Proteus) was used to simulate the circuit. The design was implemented successfully. The circuit enables real-time monitoring of stability boundaries and the corresponding margin to the observed operating point, which is used to provide a monitoring for emerging stability problems. This study was extended to introduce the fuzzy logic technique to evaluate Sag and Swell phenomena that usually precede power supply system fluctuations and malfunctions. MATLAB simulation tool was used for the present investigations of sag and swell phenomena.